2022
DOI: 10.1080/21505594.2022.2065962
|View full text |Cite
|
Sign up to set email alerts
|

The African swine fever virus protease pS273R inhibits DNA sensing cGAS-STING pathway by targeting IKKε

Abstract: African swine fever virus (ASFV), a large and complex cytoplasmic double-stranded DNA virus, has developed multiple strategies to evade the antiviral innate immune responses. Cytosolic DNA arising from invading ASFV is mainly detected by the cyclic GMP-AMP synthase (cGAS) and then triggers a series of innate immune responses to prevent virus invasion. However, the immune escape mechanism of ASFV remains to be fully clarified. The pS273R of ASFV is a member of the SUMO-1-specific protease family and is crucial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…However, the molecular mechanism of ASFV modulating the cGAS-STING pathway has not been fully elucidated. Thus, we have analyzed the effects of whole genomic open reading frames (ORFs) from ASFV China 2018/1 on the activation of cGAS-STING pathway (25), and found that p17 was able to inhibit the porcine cGAS-STING mediated IFN signaling. Our work pointed the role of p17 in the immune evasion and help understand the ASFV pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanism of ASFV modulating the cGAS-STING pathway has not been fully elucidated. Thus, we have analyzed the effects of whole genomic open reading frames (ORFs) from ASFV China 2018/1 on the activation of cGAS-STING pathway (25), and found that p17 was able to inhibit the porcine cGAS-STING mediated IFN signaling. Our work pointed the role of p17 in the immune evasion and help understand the ASFV pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Probably for this reason, ASFV encodes several genes devoted to the control of IFN-I, mainly within the MGF360 and MGF505/530 multigene families, aiming to evade host defenses (Afonso et al, 2004;Correia et al, 2013;O'Donnell et al, 2015;Reis et al, 2016). Not only that, but many other ASFV genes not belonging to these multigene families have also been involved in the modulation of the immune response, such as A238L, which inhibits the expression of TNF-alpha, the transcriptional co-activator p300 or iNOS (Granja et al, 2006a,b;Granja et al, 2008Granja et al, , 2009; I329L protein that impair the activation of IFN-β and CCL5 by inhibiting TLR3 (de Oliveira et al, 2011) or the proteins DP96R (Wang et al, 2018), S273R (Luo et al, 2022) and E120R (Liu et al, 2021), among others, which counteract IFN-I production by inhibiting cGAS-STING pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Except for the negative modulation on PTMs of TBK1, late-expressed pA137R can also mediate the autophagosome and lysosome-dependent degradation of TBK1 to block the STING-IRF3 signaling pathway [ 52 ]. Of note, ASFV-encoded pS273R, a member of the SUMO-1-specific protease family, can affect the SUMOylation of inhibitor of nuclear factor kappa-B kinase ε (Ikkε) by its catalytic activity [ 53 ]. Ikkε, a homolog of TBK1, seems to involve in the activation of STING-IRF3 signaling pathway although the mechanism is not fully clear [ 54 ].…”
Section: Suppression Of Ifn-i Production and Ifn-induced Antiviral Re...mentioning
confidence: 99%